توظيف مقاصد الشريعة في ترشيد سياسات الاقتصاد المعرفي: Utilizing Maqasid al-Shariah in the Development of Knowledge Economy Policy - عودة, جاسر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2012)
يحاول هذا البحث توظيف نظرية مقاصد الشريعة في تنمية الاقتصاد الرقمي أو المعرفي، خاصة فيما يتعلق بوضع السياسات والأولويات التنموية، والإسهام في تجنّب آثار هذا الاقتصاد السلبية في الدول الضعيفة عامة والإسلامية بوجه خاص. وبعد عرض التعريفات والتقسيمات لمقاصد الشريعة والاقتصاد المعرفي، نتساءل أولاً عن "مالية" المعلومات في ضوء مقاصد الشريعة. ثمّ نوظّف مقاصد الشريعة في تقييم معايير البنك الدولي لقياس فاعلية الاقتصاد المعرفي؛ بهدف الإسهام في تخفيف الآثار السلبية، وتصحيح الأولويات المختلة، وتعزيز القيم المتعلقة بسياسات التنمية المعرفية. This is an attempt to utilize maqasid al-shariah (purposes of the Islamic law) in the development of knowledge economy, especially in setting related developmental policies and priorities. The aim of this article is to avoid the drawbacks of ‘knowledge development’ on weak nations, especially Islamic nations. After surveying various definitions of maqasid and knowledge economy, we first ask whether information is considered ‘money’, based on the classic Islamic juridical definition. Then, we utilize the concepts of maqasid in evaluating the criteria that the World Bank uses in measuring the ‘strength’ of knowledge economies. The aim is to help correct the negative impact, balance the unfair policies, and realize the higher values in the process of the application of these criteria.